An experience report of utilizing the BPM Wheel serious game to evaluate BPM learning in higher education - Nobre, Matheus R. B.; Vilela, Jéssyka (Anais do Workshop sobre Educação em Computação (WEI); 2024: Anais do XXXII Workshop sobre Educação em Computação, 2024)
Business Process Management (BPM) is key for organizational improvement, focusing on efficiency, flexibility, and strategic alignment. Educating professionals in BPM provides them with the necessary skills for process optimization. However, there are few serious games and collaborative activities to improve BPM education, highlighting a gap in interactive learning resources. This work provides an experience report concerning applying the BPM Wheel serious game to assess the concepts of process analysis and performance indicators in a BPM discipline of the Bachelor of Information Systems at a public university. We applied the game in a 100-minute class assignment with thirty-six students divided into six teams, involving a professor and one tutor. We evaluated the students’ perceptions regarding the game through a feedback questionnaire. The results indicated a positive reception regarding the effectiveness of the BPM Wheel game in learning, with students expressing strong agreement. Additionally, they highlighted the high level of engagement provided by the serious game and a generally positive reception regarding usability.